Description of the fecal microbiota of siblings from Costa Rica with and without affective and psychotic disorders - Ouabbou Trejos, Sophie (2021)
The pathogenesis of mental disorders remains poorly understood and there are enormous challenges in the development of biomarkers and more effective therapeutic options. A total of 13 pairs of 26 siblings discordant for mental disorders, affected and unaffected, were subjected to Best Estimate Diagnosis process and clinical assessments with respect to their diagnosis, current mental health status and disability, resilience, medication, lifestyle and diet. All participants were of Hispanic ethnicity and residents of the San José Greater Metropolitan Area. Many of the pairs of siblings shared households. Affected individuals displayed major depression, bipolar affective disorder, psychosis non-otherwise specified or schizoaffective disorder. In a subsequent analysis the affected individuals were further divided according to whether they exhibited psychotic features or not. Fecal samples were collected for the analysis of the gut microbiota using 16S rRNA gene amplicon sequencing and imputed metagenomics that were compared within the sibling pairs. Based on beta-diversity analysis, the use of levothyroxine and irbesartan was identified and thus used as confounders. Decreased bacterial richness was observed among the affected participants. The relative abundances of several bacterial taxa showed significant differences, including families Peptostreptococcaceae, Ruminococcaceae, Porphyromonadaceae, and genera Pseudomonas, Barnesiella, Odoribacter, Paludibacter, Lactococcus, Clostridium, Acidaminococcus and Haemophilus. The proportion of Proteobacteria (Pseudomonas) was significantly increased in the affected individuals, while the bacterial taxa associated to healthy phenotype, such as Barnesiella and Ruminococcaceae, were depleted in individuals affected with psychosis in comparison to those without psychosis. Based on prediction functions of the gut microbiota, significant alternations were found in the pathways associated with amino acid metabolism in affected individuals in comparison to the unaffected. Our findings suggest the changes in gut microbiota composition and functionality are associated with mental health, its diagnostics, and therapeutics.